2013
DOI: 10.1007/s00420-013-0862-0
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study of environmental contamination with antineoplastic drugs in 33 Canadian hospitals

Abstract: Surface contamination by cyclophosphamide, ifosfamide and methotrexate in Canadian hospitals is improving both in terms of the proportions of positive samples and in terms of the surface concentration of antineoplastic drugs. A local 75th percentile value should be use to assess local contamination and interpret local results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…5,7 Recent evidence has confirmed that a range of Canadian health care workers are at risk of exposure. Several studies have found detectable levels of drug contamination on various work surfaces, [8][9][10] and others have demonstrated the presence of antineoplastic drugs on health care workers' hands. 11,12 These findings are noteworthy, given that the main route of exposure to antineoplastic drugs for health care workers is through skin contact.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Recent evidence has confirmed that a range of Canadian health care workers are at risk of exposure. Several studies have found detectable levels of drug contamination on various work surfaces, [8][9][10] and others have demonstrated the presence of antineoplastic drugs on health care workers' hands. 11,12 These findings are noteworthy, given that the main route of exposure to antineoplastic drugs for health care workers is through skin contact.…”
Section: Discussionmentioning
confidence: 99%
“…For calculations, concentrations that fell between the limit of detection and the limit of quantification were assigned a value corresponding to the limit of quantification divided by 2, 14 and concentrations that fell below the limit of detection were assigned a value corresponding to the limit of detection divided by 2. 15 Results from the hospitals that participated in the 3 earlier studies [10][11][12] and the current study were used for comparisons over time.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Twelve standardized measurement sites, 6 in pharmacy areas and 6 in patient care areas, were selected for sampling (Table 1). These sites were identical with those targeted in the [2008][2009][2010]2012, and 2013 studies.…”
Section: Sampling Techniquementioning
confidence: 99%
See 2 more Smart Citations